Frequency: The overlooked resistance training variable for inducing muscle hypertrophy? - Dankel, S. J.; Mattocks, K. T.; Jessee, M. B.; Buckner, S. L.; Mouser, J. G.; Counts, B. R.; Laurentino, G. C.; Loenneke, J. P. (Sports Medicine, 2017)
The principle of progressive overload must be adhered to for individuals to continually increase muscle size with resistance training. While the majority of trained individuals adhere to this principle by increasing the number of sets performed per exercise session, this does not appear to be an effective method for increasing muscle size once a given threshold is surpassed. Opposite the numerous studies examining differences in training loads and sets of exercise performed, a few studies have assessed the importance of training frequency with respect to muscle growth, none of which have tested very high frequencies of training (e.g., 7 days a week). The lack of studies examining such frequencies may be related to the American College of Sports Medicine recommendation that trained individuals use split routines allowing at least 48 h of rest between exercises that stress the same muscle groups. Given the attenuated muscle protein synthetic response to resistance exercise present in trained individuals, it can be hypothesized that increasing the training frequency would allow for more frequent elevations in muscle protein synthesis and more time spent in a positive net protein balance. We hypothesize that increasing the training frequency, as opposed to the training load or sets performed, may be a more appropriate strategy for trained individuals to progress a resistance exercise program aimed at increasing muscle size.